2006
DOI: 10.1080/01457630500522271
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Modeling Gas-Phase Flow in Microchannels: From Slip to Transition

Abstract: It has long been recognized that the fluid mechanics of gas-phase microflows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(69 citation statements)
references
References 37 publications
1
67
0
1
Order By: Relevance
“…Numerous studies include second-order velocity slip and temperature jump boundary conditions to analyze the fluid flow and heat transfer in microdevices [36][37][38][39][40][41][42][43][44][45]. The exact form of second-order slip condition and precise values of secondorder slip coefficients are not described in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies include second-order velocity slip and temperature jump boundary conditions to analyze the fluid flow and heat transfer in microdevices [36][37][38][39][40][41][42][43][44][45]. The exact form of second-order slip condition and precise values of secondorder slip coefficients are not described in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers adopted different values of slip coefficients and varying second-order slip conditions to model the flow in the slip and transition regime. Numerous second-order slip models [37][38][39][40][41][42][43] were proposed to analyze the fluid flow and heat transfer characteristics with the choice of different slip coefficients. Recently, closed form expressions were stated for the Nusselt number using second-order velocity slip and temperature jump condition [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Maxwell estimated the coefficient α s by considering that the incident gas molecules have the same distributions as those of the bulk gas, and obtained α s = √ π/2, which is typically approximated by unity. However, more rigorous kinetic analyses of the Boltzmann equation for planar flows (Cercignani & Daneri (1963)) have shown that α s = 1.1466, (for more details see Barber & Emerson (2006)). Following Maxwell's original work, many other slip models have been proposed in the literature including results for atomically rough walls, for more details see the review article by Zhang et al (2012).…”
Section: Air Flow Modelmentioning
confidence: 99%
“…However, there are large variations in the second-order slip coefficient. The lack of a universally accepted second-order slip coefficient is a major problem in extending Navier-Stokes equations into the transition regime (Barber and Emerson 2006). Muzychka and Yovanovich (2002) developed a simple model for predicting the friction factor Reynolds number product in non-circular ducts for fully developed laminar continuum flow.…”
Section: Literature Reviewmentioning
confidence: 99%